Integrating Local Wisdom into EFL Creative Writing: Students’ Perceptions of Story-Based Projects - Alvionita Damayanti; Maria Arina Luardini; Maida Norahmi; Roni Kurniawan (English Department, Universitas Negeri Surabaya, 2026)
This study investigated EFL students’ perceptions of local wisdom-based creative writing through narrative story projects. Using a descriptive qualitative design, the study involved 22 undergraduate students from the English Education Study Program at Universitas Palangka Raya who had completed a local story project in a creative writing course. Data were collected through a closed-ended questionnaire and semi-structured interviews. Questionnaire responses were analyzed using descriptive statistics, while interview data were analyzed thematically. The findings revealed two major themes: perceived benefits and challenges. Students perceived local wisdom-based creative writing as beneficial for developing creativity, increasing enjoyment, providing freedom and creative space, supporting motivation, and reducing writing anxiety. Local stories helped students generate ideas, express personal experiences, and integrate cultural knowledge into narrative texts. However, students also encountered challenges, including limited imagination, low motivation, lack of self-confidence, and concerns about grammar and language accuracy. The study suggests that local story projects can provide meaningful and culturally relevant writing experiences for EFL learners, but students still need structured guidance, linguistic support, and encouragement to balance creativity, confidence, and language accuracy.